Ageing Healthy: Perceptions of Older Persons, Community Members, and Other Stakeholders in Uganda - Eunice L. Kyomugisha MA; Rachel King PhD; Rosalind Parkes-Ratanshi PhD; Susan Nakkazi MA; Carol Brayne PhD; Louise Lafortune PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Promoting healthy ageing would benefit from an understanding of what this means to stakeholders. We explored healthy ageing perceptions in rural and peri-urban Ugandan communities. Community dialogues, focus group discussions with older persons, community members, community-based organization leaders, key informant interviews with Ministries of Gender (2), Health (1), non-governmental organizations (3) and elderly representatives (5) were held. Thematic content analysis framework was used. Physical perceptions of ageing healthy included physical fitness, absence of health challenges, good physical appearance and looking younger. Emotional perceptions were a stress-free life with children’s care, a balanced diet, basic needs and activity involvement. Socio-economic included financial stability, medical accessibility, future planning and network engagement. Spirituality, ageing with dignity and knowledge of body changes were others. The study provides insight into physical, emotional, and socio-economic perceptions of healthy ageing. Additional research in other settings would inform the UN Decade of Healthy Ageing.